Peran Guru BK dalam Upaya Menangani Penyimpangan Seksual Siswa - Ahmad Masrur Firosad (Fakultas Tarbiyah dan Keguruan UIN Imam Bonjol Padang, 2016)
The entire high school students is a teenager in which at his age he experienced the transition from kids, teens to adulthood. Many things that make teenagers irregularities, in particular is a sexual perversion, namely teenage sexual behavior before marriage dilakuakan. Teachers Counseling as a counselor at the school in existence has a strategic role in addressing these problems can fulfill their role by conducting orientrasi services, information, and guidance and counseling groups. Teacher guidance and counseling can not perform its own role but must involve all parties in addressing this issue, including school parties as the principal subject teacher and homeroom teacher, parents, the community, and the students themselves.